2020
DOI: 10.1088/1742-6596/1521/4/042064
|View full text |Cite
|
Sign up to set email alerts
|

The application of scaffolding augmented reality (AR) media in the sharing task learning of electrolyte and non-electrolyte solutions

Abstract: This research is based on the difficulty of students in understanding the abstract concept of electrolyte and non-electrolyte solutions. The aim of this study is to evaluate the improvement of students’ understanding concepts with the scaffolding of augmented reality (AR) media in the sharing task learning of electrolyte and non-electrolyte solutions. This research was conducted at one of the high schools in Bandung, Indonesia. Data were obtained through questionare understanding the concept of electrolyte and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Thus, several learning domains have been progressively aided by strategies that involve AR. A number of recent investigations with this technology have been carried out in areas such as history (Trista & Rusli, 2020), mathematics (Kang et al, 2020), physics (Abdusselam & Karal, 2020), biology (Nasongkhla et al, 2019) and chemistry (Nurrohmah et al, 2020). In chemistry, understanding the microscopic/macroscopic chemical world and abstract concepts, which involve complex subjects, such as molecular structures (Maier & Klinker, 2013a), chemical bonds (Saidin et al, 2019), and chemical reactions (Ewais & Troyer, 2019), is very challenging for students (Cai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, several learning domains have been progressively aided by strategies that involve AR. A number of recent investigations with this technology have been carried out in areas such as history (Trista & Rusli, 2020), mathematics (Kang et al, 2020), physics (Abdusselam & Karal, 2020), biology (Nasongkhla et al, 2019) and chemistry (Nurrohmah et al, 2020). In chemistry, understanding the microscopic/macroscopic chemical world and abstract concepts, which involve complex subjects, such as molecular structures (Maier & Klinker, 2013a), chemical bonds (Saidin et al, 2019), and chemical reactions (Ewais & Troyer, 2019), is very challenging for students (Cai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These proportions are close to the survey of Sırakaya and Sırakaya (2018), in which the types of instruments Interview and Observation were identified, respectively, at the rates of 13.3% and 9%. The Observation instrument was used in the study of Nurrohmah et al (2020), which aimed at evaluating the improvement of students' understanding of concepts in learning tasks of sharing electrolytic and non-electrolytic solutions. As a result, the authors concluded that AR improves understanding.…”
Section: Rq-5 What Instruments Are Used To Collect Data?mentioning
confidence: 99%